Prognostic significance of natural killer cell depletion in predicting progressive fibrosing interstitial lung disease in idiopathic inflammatory myopathies - Shao, Chenyi; Xia, Nana; Zhen, Yan; Zhang, Xueliang; Yan, Ninghui; Guo, Qiang (Frontiers in Immunology, 2024)
Abstract Objectives: Interstitial lung disease (ILD) is one of the common extramuscular involvement in idiopathic inflammatory myopathies (IIMs) (1). Several patients develop a progressive fibrosing ILD (PF-ILD) despite conventional treatment, resulting in a progressive deterioration in their quality of life (2). Here, we investigated the clinical and immune characteristics of IIM-ILD and risk factors for PF-ILD in IIM, mainly in anti-melanoma differentiation-associated protein 5 (anti-MDA5+) dermatomyositis (DM) and anti-synthetase syndrome (ASS). Methods: Here, a prospective cohort of 156 patients with IIM-ILD were included in the longitudinal analysis and divided into the PF-ILD (n=65) and non-PF-ILD (n=91) groups, and their baseline clinical characteristics were compared. Univariate and multivariate Cox analyses were performed to identify the variables significantly associated with pulmonary fibrosis progression in the total cohort, then anti-MDA5+ DM and ASS groups separately. Results: Peripheral blood lymphocyte counts, including T, B, and NK cell counts, were significantly lower in the PF-ILD group than in the non-PF-ILD group. This characteristic is also present in the comparison between patients with anti-MDA5+ DM and ASS. The multivariate Cox regression analysis revealed that age > 43.5 years [HR: 7.653 (95% CI: 2.005-29.204), p = 0.003], absolute NK cell count < 148 cells/μL [HR: 6.277 (95% CI: 1.572-25.067), p = 0.009] and absolute Th cell count < 533.2 cells/μL [HR: 4.703 (95% CI: 1.014-21.821), p = 0.048] were independent predictors of progressive fibrosing during 1-year follow-up for patients with anti-MDA5+ DM, while absolute count of NK cells < 303.3 cells/µL [HR: 19.962 (95% CI: 3.108-128.223), p = 0.002], absolute count of lymphocytes < 1.54510^9/L [HR: 9.684 (95% CI: 1.063-88.186), p = 0.044], and ferritin > 259.45 ng/mL [HR: 6 (95% CI: 1.116-32.256), p = 0.037] were independent predictors of PF-ILD for patients with ASS. Conclusions: Patients with anti-MDA5+ DM and ASS have independent risk factors for PF-ILD. Lymphocyte depletion (particularly NK cells) was significantly associated with PF-ILD within 1-year of follow-up for IIM-ILD.